Pengaruh rasio OEOI, LDR, dan EAR terhadap kinerja Bank Go Publik yang terdaftar di Bursa Efek Indonesia periode 2011-2015 - Nur Haryatri, Runi, Ihwan Susila S.E., M.Si., Ph.D (2017)
This study aimed to analyze the effect of the ratio OEOI, LDR, and EAR on the performance of the Bank. population which is the object of this study is the Bank went public listed on the Indonesia Stock Exchange. The sample used by 16 Bank went public by using purposive sampling method. The analytical method used in this research is multiple regression method. The results based on partial hypothesis test (t test) showed that oeoi variables significantly affect ROA, while variable LDR and EAR no significant effect on the ROA. The result of the coefficient of determination (R